2015
DOI: 10.2147/ppa.s86153
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infection in a teaching hospital: a prospective study of 1,138 patients

Abstract: BackgroundThe purpose of this study was to identify risk factors for surgical site infection (SSI) in a teaching hospital.MethodsA prospective study was initiated to investigate risk factors for SSI at a university-affiliated tertiary care center from July 2013 to December 2014. The chi-square test for categorical variables was used to determine the significance of association, whereas the multivariate logistic regression model was used to examine independent risk factors for SSI.ResultsA total of 1,138 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 37 publications
(38 reference statements)
8
21
4
1
Order By: Relevance
“… 1 , 17 The association between increased age and occurrence of SSIs may be attributed to a decrease in physiological defense mechanisms and immune function. 18 , 19 Surgical wound classification has been recognized as a predictive factor in developing SSIs after surgery, and the incidence of SSI can be expected in patients with a higher surgical wound class. 19 …”
Section: Discussionmentioning
confidence: 99%
“… 1 , 17 The association between increased age and occurrence of SSIs may be attributed to a decrease in physiological defense mechanisms and immune function. 18 , 19 Surgical wound classification has been recognized as a predictive factor in developing SSIs after surgery, and the incidence of SSI can be expected in patients with a higher surgical wound class. 19 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to the study by Oliveira et al, 14 who found no significant association between surgery type and SSI (p = 0.10). In contrast, a study of Cheng et al 15 showed a higher incidence of SSI in the emergency surgery group with a significant difference (p = 0.000). This study proposed that inadequate preoperative preparation of emergency surgeries may be responsible for such difference.…”
Section: Discussionmentioning
confidence: 67%
“…This showed that other factors must be evaluated alongside the surgical wound degree. 14 Cheng et al 15 evaluated risk factors of SSI in teaching hospitals. The study concluded that the degree of the surgical wound was independently associated with SSI after multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors relating to the patient, procedure and the environment also alter the odds of developing an SSI. Research has been done to identify risk factors for SSI with the hope that it will lead to preemptive action to reduce the incidence rate of SSI [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%